Environmental management and responsibility in the practices of a family agriculture cooperative: the perception of cooperative members (Research, Society and Development, 2020)
Considering that the environmental crisis has pressured organizations to change their way of acting to remain competitive in the market, and corporate social responsibility appears as a means for organizations to adapt to the "new" market of consumers concerned with environmental issues, and knowing that the cooperative is an organization with particularities, but that it operates in the market, and should be guided by activities aimed at sustainable development, the objective is to analyze the perception of cooperative members about the management and environmental responsibility in the practices of a family farming cooperative. For that, we opted for the descriptive approach, once we interviewed seven cooperative members, by means of a script composed by 12 (twelve) questions, in a five-point scale between agreeing or totally disagreeing, elaborated from the Ethos Indicators of Corporate Social Responsibility and two principles of cooperativism (fifth and seventh). Thus, it is observed that there was an unfavorable perception of the cooperative members in relation to the cooperative's environmental management, which allows the conclusion that the absence of a formal and clear environmental policy and Environmental Education program in the organization could positively influence the development of environmental actions in the cooperative.